2020
DOI: 10.3389/fonc.2020.01119
|View full text |Cite
|
Sign up to set email alerts
|

Identification of RNA: 5-Methylcytosine Methyltransferases-Related Signature for Predicting Prognosis in Glioma

Abstract: Background: Glioma is the most common primary intracranial tumor, accounting for the vast majority of intracranial malignant tumors. Aberrant expression of RNA:5-methylcytosine(m 5 C) methyltransferases have recently been the focus of research relating to the occurrence and progression of tumors. However, the prognostic value of RNA:m 5 C methyltransferases in glioma remains unclear. This study investigated RNA: m 5 C methyltransferase expression and defined its clinicopathological signature and prognostic val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 42 publications
1
32
0
Order By: Relevance
“…Studies have confirmed that m 5 C is involved in the progression of hepatocellular carcinoma (37,38). Also, there is increasing evidence that methylation regulatory factors can be used as prognostic and diagnostic markers of cancer (39)(40)(41)(42)(43). For example, the high expression of NSUN1 has been identified as a prognostic marker for non-small cell lung cancer (44)(45)(46).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have confirmed that m 5 C is involved in the progression of hepatocellular carcinoma (37,38). Also, there is increasing evidence that methylation regulatory factors can be used as prognostic and diagnostic markers of cancer (39)(40)(41)(42)(43). For example, the high expression of NSUN1 has been identified as a prognostic marker for non-small cell lung cancer (44)(45)(46).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence suggests that dysregulated aberrant RNA epigenetic modifications may function as oncogenes or tumor suppressors in carcinogenesis and cancer progression. 25 , 26 Therefore, epigenetic regulators are promising diagnostic, prognostic, and predictive biomarkers for ccRCC. Some studies have focused on m 5 C DNA methylation genes in ccRCC that could serve as potential biomarkers for cancer diagnosis and prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence indicated that m5C RNA methyltransferase-related regulators were implicated in tumorigenesis and tumor development in ovarian cancer, cervical cancer, prostate cancer, glioma, and other several tumors [ 12 , 40 ]. However, the current study did not investigate the relationship between m5C modifications and CM development.…”
Section: Discussionmentioning
confidence: 99%